Genetic Disorders 2013
DOI: 10.5772/53641
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights Into Disease Mutations of the Ryanodine Receptor

Abstract: Ca 2+ ions form important intracellular messenger molecules in nearly every cell type of the human body. Under so-called "resting" states of the cell, the concentration of Ca 2+ in the cytoplasm is extremely low (~10-7 M), but this can rapidly rise ~2 orders of magnitude when an appropriate signal is generated. Ca 2+ ions can enter the cytoplasm either from the extracellular space or from intracellular compartments, through specialized membrane proteins. These "calcium channels" are complex proteins, often con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 207 publications
(261 reference statements)
0
5
0
Order By: Relevance
“…Previously, it was reported that a single RyR1 mutation L2867G that causes malignant hyperthermia (MH) can reduce the Tm of RyR1 Repeat34 by 13 °C [44]. One common mechanism for MH or CPVT mutations is to affect the stability and cause misfolding of RyR domains, consequently causing the gain-of-function phenotype of the channel [58]. Thus, some non-conserved residues in DBM Repeat34 could cause the destabilization of the domain, which might contribute to the high activity of the channel [59].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that a single RyR1 mutation L2867G that causes malignant hyperthermia (MH) can reduce the Tm of RyR1 Repeat34 by 13 °C [44]. One common mechanism for MH or CPVT mutations is to affect the stability and cause misfolding of RyR domains, consequently causing the gain-of-function phenotype of the channel [58]. Thus, some non-conserved residues in DBM Repeat34 could cause the destabilization of the domain, which might contribute to the high activity of the channel [59].…”
Section: Resultsmentioning
confidence: 99%
“…45 The RyR gating is stimulated by Ca 2+ -induced conformational changes in the core solenoid and C-terminal domain (CTD) which lead to the couple cytoplasmic shell (poly alanine-level models) movement to pore opening (atomic-level model). 46−48 In fish, the RyR1 genes (ryraa and ryrab) are the predominant genes expressed in the skeletal muscle, controlling the calcium release from intracellular stores, 49,50 and these interactions influence important aspects of the Ca 2+ channel function that either are essential for excitation−contraction coupling (ECC) or finetune the spatial and temporal spread of Ca 2+ signals in myocytes. 51 Several investigations also show that muscle damage and progression disorders are mediated by RyRs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The composition of RyRs macromolecular complexes is therefore an important checkpoint that induces diverse actions of Ca 2+ signaling by noncoplanar TCS in tissues and cells. ,, However, the fundamental conclusions of structure and function of RyRs in health and disease are limited. Recently, because of advances in single-particle cryogenic electron microscopy (cryo-EM), Santulli et al were able to detect for the first time the atomic-level structures of RyR. The RyR gating is stimulated by Ca 2+ -induced conformational changes in the core solenoid and C-terminal domain (CTD) which lead to the couple cytoplasmic shell (poly alanine-level models) movement to pore opening (atomic-level model). In fish, the RyR1 genes ( ryraa and ryrab ) are the predominant genes expressed in the skeletal muscle, controlling the calcium release from intracellular stores, , and these interactions influence important aspects of the Ca 2+ channel function that either are essential for excitation–contraction coupling (ECC) or fine-tune the spatial and temporal spread of Ca 2+ signals in myocytes . Several investigations also show that muscle damage and progression disorders are mediated by RyRs. …”
Section: Resultsmentioning
confidence: 99%
“…While examining the hotspots located in the RYR1 3D protein folding map, it is interesting that all the hotspots are located at the inner face of the channel. The RyR1 channels with those hotspot mutations have significantly lowered threshold for activation by Ca 2+ and increased threshold for inactivation by Ca 2+ [ 13 ]. In this context, DHPLC is a useful and efficient method for mutation screening in a large number of sequences, with high sensitivity when used to identifying various inherited diseases [ 14 ].…”
Section: Discussionmentioning
confidence: 99%